Analisis Kemampuan Guru Dalam Membuat Media Pembelajaran Sederhana - Adillah Herni; Andella Umami; Regina Khairinnisa; Iskar Prayoga; Wismanto Wismanto (Lembaga Pengembangan Kinerja Dosen, 2024)
Learning media is one of the key components of education which plays an important role in the teaching and learning process. The use of learning media is an important part that requires special attention from teachers in learning activities. There is a need to create learning media that aims to create an orderly, conducive classroom atmosphere and enable effective learning. The aim of the research is to identify teachers' abilities in creating teaching media materials. It is hoped that if teachers have the ability to create teaching material media, the teaching and learning process can run according to plan. This research uses a qualitative method based on library research, the main data sources come from books, magazines and recent journal articles related to the theme of this research. The results of this research show that the majority of teachers have not been creative in creating learning media, this is indicated by the fact that many teachers still use the lecture method in the learning and teaching process, so that the teaching and learning process seems monotonous in only one direction. It is hoped that the publication of this article will encourage teachers to be creative in making interesting learning media even though they are made with simple media.